The design of special woven-preformed structures for the high-performance film cooling with undamaged fibers based on 2.5D ceramic matrix composites. (1st March 2022) - Zhao, Chenwei; Tu, Zecan; Mao, Junkui; Chen, Pingting; Li, Longkai
Abstract: A design-manufacturing integration method for the film cooling of 2.5D woven ceramic matrix composites (CMC) is proposed which can concurrently achieve film holes with undamaged fibers and improve cooling performance. Meanwhile, this study investigates the effect of different woven-preformed structures on gas-thermal-mechanical characteristics. The design-manufacturing integration method implements the collaborative design of the micro woven structure and macroscopical shaping of film holes. Firstly, the unique micro woven method can manufacture the film holes without damaged fibers which effectively guarantees the strength of CMC. Secondly, the macroscopically shaped special woven-preformed holes (SWPHs) own the special structural features related to woven structure. These special structures change the flow field and induce the counter-rotating/anticounter-rotating Vortex Pair (CVP/Anti-CVP) which effectively improves the cooling performance and controls the thermal stress. Compared with traditional drilled cylindrical hole DCH, the SWPHs' maximum increase of averaged overall film cooling effectiveness reaches 110%. Besides, SWPHs avoid the large temperature difference between the yarn and the matrix around the drilled DCH which eventually reduces the thermal stress in the corresponding area.